Listeria monocytogenes 10403S Arginine Repressor ArgR Finely Tunes Arginine Metabolism Regulation under Acidic Conditions - Cheng, Changyong; Dong, Zhimei; Han, Xiao; Sun, Jing; Wang, Hang; Jiang, Li; Yang, Yongchun; Ma, Tiantian; Chen, Zhongwei; Yu, Jing; Fang, Weihuan; Song, Houhui (Frontiers in Microbiology, 2017)
Listeria monocytogenes is able to colonize human and animal intestinal tracts and to subsequently cross the intestinal barrier, causing systemic infection. For successful establishment of infection, L. monocytogenes must survive the low pH environment of the stomach. L. monocytogenes encodes a functional ArgR, a transcriptional regulator belonging to the ArgR/AhrC arginine repressor family. We aimed at clarifying the specific functions of ArgR in arginine metabolism regulation, and more importantly, in acid tolerance of L. monocytogenes. We showed that ArgR in the presence of 10 mM arginine represses transcription and expression of the argGH and argCJBDF operons, indicating that L. monocytogenes ArgR plays the classical role of ArgR/AhrC family proteins in feedback inhibition of the arginine biosynthetic pathway. Notably, transcription and expression of arcA (encoding arginine deiminase) and sigB (encoding an alternative sigma factor B) were also markedly repressed by ArgR when bacteria were exposed to pH 5.5 in the absence of arginine. However, addition of arginine enabled ArgR to derepress the transcription and expression of these two genes. Electrophoretic mobility shift assays showed that ArgR binds to the putative ARG boxes in the promoter regions of argC, argG, arcA and sigB. Reporter gene analysis with gfp under control of the argG promoter demonstrated that ArgR was able to activate the argG promoter. Unexpectedly, deletion of argR significantly increased bacterial survival in BHI medium adjusted to pH 3.5 with lactic acid. We conclude that this phenomenon is due to activation of arcA and sigB. Collectively, our results show that L. monocytogenes ArgR finely tunes arginine metabolism through negative transcriptional regulation of the arginine biosynthetic operons and of the catabolic arcA gene in an arginine-independent manner during lactic acid-induced acid stress. ArgR also appears to activate catabolism as well as sigB transcription by anti-repression in an arginine-dependent way.